Issue Information TOC. Issue 1 (16th September 2019) - Unknown
Abstract : Cover : In Prandi and Demichelis (https://doi.org/10.1002/cpbi.81 ), the image shows a cartoon of the computation of beta and allelic fraction of informative SNPs. (A ) Example of the allelic fraction (AF) and beta (β) values computed for five genomic positions (p1 to p m ) corresponding to five informative SNPs. Positions p1 to p n are within a hemizygously deleted genomic segment, A, whereas genomic positions p n + 1 to p m lie within a wild‐type genomic segment, B. (B to D ) Examples of a normal cell and two different tumor cells. Tumor cells 1 and 2 differ in the status of genomic segment B. Histograms below the cell cartoons report the expected distribution of the AF of SNPs in genomic segments A and B together with the associated beta values. (E and F ) Examples of two different tumor samples. Tumor sample 1 includes one normal cell and nine tumor cells with deleted genomic segment A and wild‐type genomic segment B. Tumor sample 2 differs from tumor sample 1 in the presence of six tumor cells with a hemizygous deletion of genomic segment B. Expected distribution of the AF of informative SNPs together with estimated beta are depicted below each tumor sample cartoon.